OUTSOURCHING (ALIH DAYA) DAN PENGELOLAAN TENAGA KERJA PADA PT INDOFARM SUKSES MAKMUR MENURUT UNDANG-UNDANG NO 13 TAHUN 2003 (TENTANG KETENAGAKERJAAN) - Dody Partogi Nadeak; Anissa Zahra; Luhut Leonard; Said Rizal (The Juris, 2021)
Protection Rules that apply to workers As the fulfillment of inherent core rights & there are those regulated in the constitution contained in one of the articles in the 1945 Constitution, due to the entry into force of employers as if accepting legalization, implementing outsourcing practices without paying attention to things that are stopped by the law. The primary reason for outsourcing for companies is to increase business concentration because operational activities have been delegated to other parties. This study will analyze the main main conflicts that are in sync with the title using the scope of the problem that is currently happening, as described above using a normative juridical approach. laws and regulations in this study. The data obtained are included in the form of a concept model which will be the primary basis for analyzing. As for the writing of this scientific paper, the method used to analyze the data has been taken using a descriptive (non-statistical) method. Legislation that contains the content of manpower as the basis for steps to regulate the lower limit of workers' salaries to create and for the welfare of workers in North Sumatra Province. it is not working properly. The role of laws and regulations on how to set the lower limit of wages cannot help workers to achieve labor sufficiency.